A review of Battery Electric Vehicle technology and readiness levels. (October 2017) - Mahmoudzadeh Andwari, Amin; Pesiridis, Apostolos; Rajoo, Srithar; Martinez-Botas, Ricardo; Esfahanian, Vahid
Abstract: As concerns of oil depletion and security of supply remain as severe as ever, and faced with the consequences of climate change due to greenhouse gas emissions, Europe is increasingly looking at alternatives to traditional road transport technologies. Battery Electric Vehicles (BEVs) are seen as a promising technology, which could lead to the decarbonisation of the Light Duty Vehicle fleet and to independence from oil. However it still has to overcome some significant barriers to gain social acceptance and obtain appreciable market penetration. This review evaluates the technological readiness of the different elements of BEV technology and highlights those technological areas where important progress is expected. Techno-economic issues linked with the development of BEVs are investigated. Current BEVs in the market need to be more competitive than other low carbon vehicles, a requirement which stimulates the necessity for new business models. Finally, the all-important role of politics in this development is, also, discussed. As the benefit of BEVs can help countries meet their environmental targets, governments have included them in their roadmaps and have developed incentives to help them penetrate the market.